The Cultural Condition of Speech Community and Linguistic Signs in What a Girls Movie - Areta Puspa (Pendidikan Fisika FKIP UNEJ, 2017)
Abstract: Language definitely portrays its communal or societal features of the community from which it emerges. This robust relation is evident both in the deep structure and in the surface structure of certain language, which at last incurs language particularities. Those language particularities robustly stipulate the communal or societal bonding by which someone is deliberately demanded to forge his personal conscience with the shared appropriateness of the community he wishes to mingle with. As a result, a single language speaker may possess a number of socio-linguistic repertoires, each of which is coloured by different communities. These linguistic repertoires apparently go beyond the societal or communal demands in as much as educational, political, economic, and professional motives also have bearing impact on the repertoires to rely on. This paper is intended to unearth the speech community and linguistic signs embedded in the movie entitled What A Girl Wants. Specifically, it emphasizes on analyzing the social differences in terms of linguistic repertoires and shared appropriateness. As a further analysis on communal bonding, it was also revealed that individuals have the liberty to either procure or repudiate particular social identity attributed to them regardless the fact that there are some situational demands in particular social context. Key words: language, identity, communities, appropriateness, and bonding